MARKET BASKET ANALYSIS TO IDENTIFY STOCK HANDLING PATTERNS & ITEM ARRANGEMENT PATTERNS USING APRIORI ALGORITHMS - Prawira, Tresna Yudha; Sunardi, Sunardi; Fadlil, Abdul (Khazanah Informatika, 2020)
The process of managing the pattern of handling stock of goods and the pattern of arranging goods on store shelves requires an identification process by utilizing data from sales transaction results. Market basket analysis of sales transaction data using Apriori Algorithm stages produces an information in the form of association rules with a minimum support value of 50% and a minimum confidence of 60%. It can be a reference in the arrangement of items on store shelves by referring to a combination of items that are often bought by consumers simultaneously. In addition, the stock inventory pattern can take advantage of the results of determining the high frequency value in the combination pattern 1 - itemset C1 with a minimum support value of 50% which is compared with the initial inventory.